Gay Men at Midlife and Adult Learning: An Uneasy Truce with Heteronormativity - Thomas V. Bettinger (Adult Education Research Conference, 2007)
Thirteen gay men between the ages of 40 and 60 relate stories of their lived experiences, demonstrating both adherence and resistance to heteronormative societal expectations regarding aging gay men. Their stories have implications for adult development and adult education, two fields in which this group has largely been ignored.